ENHANCING STUDENTS’ ACADEMIC ACHIEVEMENT THROUGH EFFECTIVE TEACHER PERFORMANCE - Agusalim (JEC (Jurnal Edukasi Cendekia), 2024)
Teacher performance management plays a strategic role in determining the quality of the learning process and student outcomes, especially at the elementary school level. Teachers function not only as knowledge transmitters but also as planners, implementers, and evaluators of learning. This study aims to describe how teacher performance management, which includes lesson planning, teaching implementation, and work motivation, contributes to improving the learning outcomes of fourth-grade students at SD Negeri 3 Lamangga. The research employed a qualitative approach using a descriptive method. Data were collected through interviews, observations, and documentation, with the main informants being the fourth-grade teacher and the principal. The results show that teachers who prepare structured lesson plans can create more effective learning environments. Active and innovative classroom instruction encourages greater student participation and deeper understanding of the subject matter. In addition, teachers with strong work motivation demonstrate discipline and a sense of responsibility that positively influence students’ enthusiasm for learning. In conclusion, effective teacher performance management has a significant impact on improving student learning outcomes and should be a major focus in primary education management.